Secure lightweight CAN protocol handling for electric vehicles - Hanchate, Vandana Vijaykumar; Kamathe, Rupali; Deshpande, Meghana; Joshi, Kalyani; Borde, Sheetal; Inamdar, Abrar; Madduru, Vijayalakshmi (Institute of Advanced Engineering and Science, 2025)
The integrity of controller area network (CAN) protocols in electric vehicles (EVs) is of paramount importance, due to their susceptibility to cyber intrusions and unauthorized access. Traditional encryption-based security solutions, such as advanced encryption standard (AES) and anomaly detection methods, often introduce high computational overhead and latency, making them unsuitable for real-time EV communication. This study proposes a secure lightweight CAN protocol (SLCP), implemented using ARDUINO Uno and MCP2515, which enhances message integrity, authentication, and fault recovery without compromising system efficiency. Experimental testing demonstrated that the proposed SLCP reduces message authentication latency by 25% and improves message integrity by 40% compared to conventional encryption techniques. Additionally, packet resynchronization time was reduced by 30%, ensuring minimal disruptions in case of message loss. These findings establish SLCP as a viable, real-time alternative for low-power EV communication networks. The study contributes to advancing lightweight security frameworks for EV networks, paving the way for scalable, real-time cybersecurity solutions in modern electric transportation.